Perinatal Ischemic Stroke: a Five-Year Retrospective Study in a Level-III Maternity - Machado, V (2015)
Objective To study the incidence, clinical presentation, risk factors, imaging diagnosis, and clinical outcome of perinatal stroke. Methods Data was retrospectively collected from full-term newborns admitted to the neonatal unit of a level III maternity in Lisbon with cerebral stroke, from January 2007 to December 2011. Results There were 11 cases of stroke: nine were arterial ischemic stroke and two were cerebral venous sinus thrombosis. We estimated an incidence of arterial ischemic stroke of 1.6/5,000 births and of cerebral venous sinus thrombosis of 7.2/100,000 births. There were two cases of recurrent stroke. Eight patients presented with symptoms while the remaining three were asymptomatic and incidentally diagnosed. The most frequently registered symptoms (8/11) were seizures; in that, generalized clonic (3/8) and focal clonic (5/8). Strokes were more commonly left-sided (9/11), and the most affected artery was the left middle cerebral artery (8/11). Transfontanelle ultrasound was positive in most of the patients (10/11), and stroke was confirmed by cerebral magnetic resonance in all patients. Electroencephalographic recordings were carried out in five patients and were abnormal in three (focal abnormalities n=2, burst-suppression pattern n=1). Eight patients had previously identified risk factors for neonatal stroke which included obstetric and neonatal causes. Ten patients were followed up at outpatients setting; four patients developed motor deficits and one presented with epilepsy. Conclusions Although a modest and heterogeneous sample, this study emphasizes the need for a high level of suspicion when it comes to neonatal stroke, primarily in the presence of risk factors. The prevalence of neurological sequelae in our series supports the need of long-term follow-up and early intervention strategies.